ANALISIS KONTRIBUSI PANTAI 9 DALAM VISIT SUMENEP 2018 - Evi Malia; Hanafi Hanafi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2019)
This research aim to analyze how big contribution of 9 beachinto "Visit Sumenep2018". Reaserch method in this study is a qualitative method, data collection methodsusing Taylor and Bodgan Theorys while data analysis using miles and hubberman theory.The results of this reaserch indicate that 9 beach give some contribution to succeed theVisit Sumenep 2018 program is divided into some kinds, the first is contribution ineconomic development like transportation, and new jobs like tour guide and more shopswho sells food and souvenir. But this contribution is still low and un optimally becausenothing local wisdom souvenir and food who selling. While the allocation of village fundissued for the development of 9 beach is since 2018, since 9 beach belongs to BUMDes.The government's participation in involving 9 beach is by incorporating it into a flattourist destination visit sumenep 2018.